Resource management framework for virtual data center embedding based on software defined networking. (May 2017) - Ma, Jianqiang
Abstract: In cloud computing, service providers can lease resources as needed from infrastructure providers and deploy services. Service providers only need to focus on their own services without considering the equipment cost and maintenance cost. However, traditional infrastructure providers do not guarantee the network performance and bandwidth and only provide resources with virtual machines. With the development of isolation network virtualization technology, especially the concept of software defined network, some researchers suggested that infrastructure providers should provide resources to service providers with the way of virtual data centers so as to solve these problems in the traditional data centers. Although there are many advantages to allocate resources with virtual data centers, it also brings a new challenge that how to meet the diverse needs of service providers and allocate resources at the minimum cost and maximum profit. In order to solve the embedding problem of virtual data centers based on software defined networking (SDN), this paper presents a novel resource management framework for the embedding problem of virtual data centers. It is a heuristic embedding algorithm based on topological potential and modularity and used to improve the acceptance ratio and the infrastructure providers' revenue. Finally, a dynamic monitoring strategy is proposed to select the virtual data center request with a high revenue cost ratio and further maximize the profit of infrastructure providers. A large number of simulation experiments prove that the proposed algorithm can accept more requests with the minimum cost, and improve the revenues of infrastructure providers.